Benchmark Study. The Agricultural Technology Development Fund for Contract Research: An INIA (Uruguay) Initiative - Hobbs, S. Huntington; Valverde, Carlos; Indarte, Eduardo; Lanfranco, Bruno (International Service for National Agricultural Research, 1998)
This Briefing Paper is the fourth of ISNAR's benchmark studies. It describes how Uruguay's national institute for agricultural research (INIA) introduced a novel way of strengthening agricultural research in the country by creating a competitive fund called FPTA (agricultural technology development fund) to help finance research done outside INIA, by non-INIA researchers. INIA manages the fund and selects the projects to be supported. FPTA has proved to be an excellent tool for establishing strategic alliances with other agricultural research organizations and institutes in Uruguay. One of the factors explaining the success of the initiative is the strong political support it receives from the whole agricultural sector. Another factor is the two-year limit on FPTA projects, which encourages researchers to focus on practical results. FPTA is also an effective mechanism for coordinating the country's various research efforts and for enhancing the impact of INIA's own research. In presenting INIA's FPTA as a benchmark, ISNAR hopes to inspire research organizations in other developing countries to copy or adapt aspects of this experience with a view to improving their own agricultural research management practices and results.